Non-profit Sector and Charity Financing: Mapping the Field - Marie Hladká, Vladimír Hyánek (Littera Scripta, 2015)
The issue of charitable giving has been central to the interest of researchers in the international field for several decades. Charitable giving is closely connected with economic policy and directly affects issues within civil society with regards to the financing of the third sector (non-profit organizations). The objective of this paper is to carry out a critical exploration of the facts based on a review of theories and data sources relating to charitable giving, as well as the volume and structure thereof. The search for and submission of appropriate explanatory paradigms enables the subject of charitable giving to be conceptually anchored, which in turn enables us to determine a theoretically grounded set of variables for it. Following on from these intellectual developments in the given area, this paper maps the current state of empirical knowledge in the Czech Republic.